Variations in serum electrolyte concentrations and renal function after therapeutic hip arthroscopy: a pilot study - Verhelst, Luk; De Schepper, Jo; Sergeant, Gregory; Liekens, Koen; Delport, Hendrik (Arthroscopy, 2009)
The purpose of this study was to analyze changes in serum electrolyte concentration and renal function after hip arthroscopy. We studied 10 consecutive patients (4 men and 6 women; median age, 30.5 years [range, 20 to 50 years]) undergoing hip arthroscopy. Operating time, traction time, and perfusion volume of lactated Ringer solution (in milliliters) were recorded. Preoperative and postoperative levels of sodium (Na(+)), potassium (K(+)), cloride (Cl(-)), calcium (Ca(2+)), magnesium (Mg(2+)), phosphorous (P), creatinine, and blood urea nitrogen (BUN) were compared. The median operating time was 80 minutes (range, 60 to 150 minutes). The median perfusion volume of lactated Ringer solution was 15,000 mL (range, 6,000 to 30,000 mL). The median traction time was 37.5 minutes (range, 30 to 105 minutes). None of the patients had postoperative complications develop. With a mean decrease of 0.84 +/- 0.68 mg/dL, only serum calcium levels were found to decrease significantly (P = .01). There was a mean decrease of 1.50 +/- 2.07 mEq/L in sodium concentrations (P = .06). Hip arthroscopy was associated with a mean postoperative decrease in creatinine and BUN concentrations of 0.05 +/- 0.06 mg/dL (P = .19) and 9.84 +/- 10.36 mg/dL (P = .13), respectively. Although the mean decrease in BUN concentration was important, this was not shown to be significant. No correlations were found between operating time, perfusion volume, and postoperative changes. Lengthy therapeutic hip arthroscopy under high intra-articular pressure has only a minimal effect on electrolyte balance and renal function. We therefore conclude that performing routine preoperative and postoperative blood analysis of electrolyte concentrations and renal function is unnecessary. Level IV, therapeutic case series.